Exchange Interactions on the Highest-Spin Reported Molecule: The Mixed-Valence fe42 Complex - Venegas-Yazigi, D; Venegas-Yazigi, D; Aravena-Ponce, D; Aravena-Ponce, D (Nature Publishing Group, 2016)
The finding of high-spin molecules that could behave as conventional magnets has been one of the main challenges in Molecular Magnetism. Here, the exchange interactions, present in the highestspin molecule published in the literature, Fe42, have been analysed using theoretical methods based on Density Functional Theory. The system with a total spin value S = 45 is formed by 42 iron centres containing 18 high-spin FeIII ferromagnetically coupled and 24 diamagnetic low-spin FeII ions. The bridging ligands between the two paramagnetic centres are two cyanide ligands coordinated to the diamagnetic FeII cations. Calculations were performed using either small Fe4 or Fe3 models or the whole Fe42 complex, showing the presence of two different ferromagnetic couplings between the paramagnetic FeIII centres. Finally, Quantum Monte Carlo simulations for the whole system were carried out in order to compare the experimental and simulated magnetic susceptibility curves from the calculated exchange coupling constants with the experimental one. This comparison allows for the evaluation of the accuracy of different exchange-correlation functionals to reproduce such magnetic properties.